Angle-ply biomaterial scaffold for annulus fibrosus repair replicates native tissue mechanical properties, restores spinal kinematics, and supports cell viability - Borem, Ryan (Acta Biomater, 2017)
Annulus fibrosus (AF) damage commonly occurs due to intervertebral disc (IVD) degeneration/herniation. The dynamic mechanical role of the AF is essential for proper IVD function and thus it is imperative that biomaterials developed to repair the AF withstand the mechanical rigors of the native tissue. Furthermore, these biomaterials must resist accelerated degradation within the proteolytic environment of degenerate IVDs while supporting integration with host tissue. We have previously reported a novel approach for developing collagen-based, multi-laminate AF repair patches (AFRPs) that mimic the angle-ply architecture and basic tensile properties of the human AF. Herein, we further evaluate AFRPs for their: tensile fatigue and impact burst strength, IVD attachment strength, and contribution to functional spinal unit (FSU) kinematics following IVD repair. Additionally, AFRP resistance to collagenase degradation and cytocompatibility were assessed following chemical crosslinking. In summary, AFRPs demonstrated enhanced durability at high applied stress amplitudes compared to human AF and withstood radially-directed biaxial stresses commonly borne by the native tissue prior to failure/detachment from IVDs. Moreover, FSUs repaired with AFRPs and nucleus pulposus (NP) surrogates had their axial kinematic parameters restored to intact levels. Finally, carbodiimide crosslinked AFRPs resisted accelerated collagenase digestion without detrimentally effecting AFRP tensile properties or cytocompatibility. Taken together, AFRPs demonstrate the mechanical robustness and enzymatic stability required for implantation into the damaged/degenerate IVD while supporting AF cell infiltration and viability.